Implementation of an in‐house quantitative real‐time polymerase chain reaction method for Hepatitis B virus quantification in West African countries. Issue 11 (29th June 2016) - Ghosh, S.; Sow, A.; Guillot, C.; Jeng, A.; Ndow, G.; Njie, R.; Toure, S.; Diop, M.; Mboup, S.; Kane, C. T.; Lemoine, M.; Thursz, M.; et al.
Summary: Hepatitis B virus (HBV) is a major cause of chronic liver disease worldwide. HBV infection is diagnosed by serological tests, while real‐time polymerase chain reaction (qRT‐PCR) assays are used to quantify viral load, which is a crucial parameter to determine viral replication and to monitor antiviral treatments. However, measuring viral load in resource‐limited countries remains nonsystematic, due to the high cost of commercial kits. Here, we describe the development, validation and implementation of a low‐cost, in‐house qRT‐PCR assay to monitor HBV viral load in chronic carriers enrolled in the PROLIFICA programme in the Gambia and Senegal. Over 1500 HBsAg‐positive patients, including 210 chronically infected HBV patients, who were given antiviral treatment (tenofovir), were monitored by qRT‐PCR using the SYBR Green‐ and HBV‐specific primers. Twenty‐four tenofovir‐treated patients were followed up and their viral load was tested every 3 months over the 12‐month experimental time course. Compared to commercial assays, our in‐house assay was shown to be (i) highly reliable, with good intra‐ and interassay reproducibility over a wide range (45–4.5 × 10 8 copies mL −1 ), (ii) very similar in the viral loads detected (R 2  = .90), (iii) highly sensitive, as it detected loads as low as 30 copies mL −1 (~5 IU mL −1 ), (iv) cheaper (2‐ to 3‐fold), (v) easier to implement and (vi) more rapid. Based on our experience, we recommend this assay as a reliable alternative to commercial assays, for monitoring HBV viraemia in resource‐limited, highly endemic countries to reduce the cost and technical obstacles associated with commercial kits.